Effects of preferential social associations on pigs’ response to weaning - I. Camerlink; K. Scheck; T. Cadman; J.-L. Rault (Animal, 2023)
Farm animals can form preferential associations within their social group. Research has shown that the presence of familiar conspecifics can help to cope with stressful situations. Nonetheless, whether the strength of the relationship matters is largely unknown. Our aim was to investigate the influence of the strength of the social relationship between familiar partners during a stressful event. Pigs (n = 116) were observed pre-weaning for their social interactions and spatial proximity with littermates. From this, preferential associations were calculated based on sociality indices of non-agonistic social behaviours (SIsoc) and spatial proximity (SIprox). Pigs were weaned into groups of unfamiliar pigs together with one littermate. The partner was selected based on the strength of their relationship pre-weaning, with pairs from across the SIsoc and SIprox distribution. SIprox and non-agonistic social behaviour (SIsoc) were included in the statistical analysis as measures of relationship strength. Focal pigs were observed postweaning for their social behaviour and spatial proximity, skin lesions and growth, and salivary cortisol concentration pre-weaning and at 4 h and 48 h postweaning. The strength of the social relationship pre-weaning did not significantly influence the behaviour or proximity towards the familiar partner postweaning, or the amount of skin lesions or weight gain. Pigs who were weaned with a littermate with whom they were strongly affiliated based on active social behaviour (SIsoc) tended to have a lower proportional increase in their cortisol concentration after weaning (P = 0.07). Pigs differed in their behaviour towards the familiar partner as compared to the unfamiliar pigs, by directing more aggression towards unfamiliar pigs (P < 0.001), and more non-agonistic social behaviours towards the familiar pig (P < 0.001). The familiar partner was on average in 12.2% of the observations the nearest neighbour, which in small groups did not differ from random choice while in large groups, this occurrence was higher than expected by chance. The results show that pigs clearly distinguish between familiar and unfamiliar pigs, but that the strength of the relationship with a familiar partner seems to have limited effects at weaning. Although preferential associations in young pigs seem weak, studies on older pigs are needed to investigate whether this is due to the relatively little time they have to establish social preferences prior to weaning.